Are there peas in a pod when considering mobile phone and mobile applications use: A quantitative study. (July 2020) - Ameen, Nisreen; Shah, Mahmood Hussain; Sims, Julian; Choudrie, Jyoti; Willis, Robert
Abstract: Despite the acknowledgement of the significance of income, affordability and cultural factors in using mobile phones research, there are few studies on how these factors affect females' use of mobile technology. Hence, this paper aims to expand knowledge on female consumers' use of mobile phones and mobile applications in developing countries. It develops a model based on combining the extended unified theory of acceptance and use of technology and the cultural influence model. Multi-stage cluster sampling was used to distribute hard copy questionnaires in Jordanian, Iraqi and UAE households led to 629 replies from female consumers. The results indicated that although income is an important factor, cost is not the highest barrier for females. Culture, society, national IT development and inclusive policies play a key role. This study contributes to existing literature by proposing a new integrated model acknowledging the role of income for females' use of mobile phones. Highlights: Companies use mobile technology to communicate with their customers. Females in low- and middle-income countries are less likely to have a mobile phone. A new model on female consumers' use of mobile phones is developed. Although income is important, cost is not the highest barrier for female consumers. Culture, information technology development and inclusive policies play a key role.